MODEL EVALUASI KIRIKPATRICK DAN APLIKASINYA DALAM PELAKSANAAN PELATIHAN (LEVEL REAKSI DAN PEMBELAJARAN) DI PUSAT PENDIDIKAN DAN PELATIHAN PERUM JAKARTA - Aminah, Hania (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
MODEL EVALUASI KIRIKPATRICK DAN APLIKASINYADALAM PELAKSANAAN PELATIHAN (LEVEL REAKSI DAN PEMBELAJARAN)DI PUSAT PENDIDIKAN DAN PELATIHAN PERUM JAKARTAHania AminahFakultas Ekonomi, Universitas Negeri JakartaEmail: haniaaminah@gmail.comABSTRACTIn order to avoid the inefficiency of the training, the training should be measured. Theresearch aim to determine the effectiveness of information and training through theimplementation of the evaluation model is to implement two levels which consist of reactionsand learning levels, using Kirkpatrick’s model. This research was conducted at the Learningand Training Center of Central Jakarta, with a sample of all participants of training. Datacollection using a questionnaire that has been tested by using content validity, whereas testsuse SPSS.The results showed that the reaction of trainees are satisfied with the implementation of thetraining that was conducted and the results are good and improving learning are assessedfrom the pre-test and post-test. The resulting increase in the difference was significant, butwhen viewed from the aspect of knowledge, understanding and application, the result of thedifference increased, but not significantly.Keywords: Training, Evaluation, Kirkpatrick Model, Employees